Machines de théâtre et théâtres-machines des années 1960-1970 - Sandrine Dubouilh (In Situ)
In 1961, at a conference held at Royaumont, the painter and set designer Rene Allio announced a principle which has become a rule, that of the theatre ‘as an instrument’. He was pleading for the effectiveness of the tools of the stage set during a time when the traditions of the ‘théâtre à l’italienne’ were being called into question. Attempts to create the experimental machineries in harmony with the aspirations of the time were rare however, and rarely crowned with success. From this period, only the Amiens Maison de la Culture still keeps a physical vestige which, in theory, could still be used. But managing the regular activity of a theatre leaves little room for the conservation of stage sets that are badly adapted or dysfunctional. At the same time, however, if these artifacts disappear, they will render invisible the traces of a history rich in its interrogations and experimentation.